Microwave Assisted Synthesis and Antimicrobial Activities of Some 2-Amino-4-aryl-3-cyano-6-(4’-hydroxy phenyl)-pyridines - Priya Gothwal; Gunwanti Malhotra; Y. K. Srivastava (E-Journal of Chemistry)
4’-Hydroxy chalcones were treated with malononitrile in the presence of ammonium acetate under solventless microwave assisted condition to get 2-amino-4-aryl-3-cyano-6-(4’-hydroxy phenyl)-pyridines. The prepared compounds were screened for their antimicrobial activity; some of them have exhibited promising antimicrobial activity.